PATH-22. THE DEVELOPMENT OF A NEW ASSAY TO MEASURE 2-HYDROXYGLUTARATE (2-hg) ENANTIOMER LEVELS AND THE UTILITY OF 2-hg AS A BIOMARKER FOR MANAGEMENT OF IDH MUTANT GLIOMAS. (5th November 2018) - Strain, Shinji; Groves, Morris; Emmett, Mark
Abstract: The isocitrate dehydrogenase (IDH) gene is mutated in a large percentage of gliomas and produces the oncometabolite, (R)-2-hydroxgylutarate [(R)-2hg]. However, no correlation between total 2hg levels and clinical parameters, like tumor burden, in glioma patients has been identified. This lack is likely due to the presence of significant levels of the enantiomer, (S)-2-hydroxyglutarate [(S)-2hg]. (S)-2hg is normally produced in the body and during hypoxic conditions. Past studies measuring 2hg via mass spectrometry methods either do not differentiate between (R)-and (S)-2hg, both which are normally detectable in serum, or use LC-MS based assays that lack the sensitivities needed to detect changes in (R)-2hg when an IDH mutant glioma is present. In this study, a novel gas chromatography-mass spectrometry method was built to measure 2hg enantiomers and used to determine if serum levels of (R)-2hg:(S)-2hg, or absolute levels of (R)-2hg, could provide clinical utility as a biomarker in patients with IDH mutant gliomas. The derivatization, fragmentation, and quantitation scheme was optimized for sensitive detection of basal 2hg enantiomers using normal human serum. Serum was then collected from patients with IDHmut and IDHwt gliomas and analyzed to measure levels of 2hg enantiomers before and during the course of treatment. The ratio of (R)-2hg:(S)-2hg was increased in a number of patients with actively growing IDHmut tumors, but not in patients with stable IDHmut tumors or IDHwt tumors. These preliminary results demonstrate the utility of the GC-MS assay for measurement of 2hg enantiomers and their ratio as a biomarker for active disease in patients with IDHmut gliomas.